The Implementation of Full-time Schools: The Situation in the Federal State of Sao Paulo (Brazil) - Rogério Adolfo de Moura (Social Work & Society, 2009)
During the past years, Brazil has been mentioned internationally as a one of the so-called BRICs (Brazil, Russia, India and China). These countries have been taking increasing space in the economical and political global scenarios in the XXI century. The facts that they possess a vast territory and stand among the highest populated countries increase their relevance within the United Nations. Besides, three of them constitute nuclear powers and two of them belong to the United Nations Security Council. Brazil has significantly participated in forums such as WTO and UNO, representing central political articulation and stability to Latin America and in the structuring and growth of MERCOSUL (Brazil, Argentina, Uruguay, Paraguay and Venezuela). Once again among the ten greatest economies of the world, the country has launched ambitious poverty-fighting programs helping more than 20 million people in the last years, such as the "Bolsa Família" (Familienstipendium) Program or and its complements).